Formation of Ag nanowires in the presence of tannic acid - Nurul Akmal, Che Lah; Aqilah, Kamaruzaman (Elsevier Ltd, 2019)
Silver nanowires (AgNWs) have received considerable attention from both research in industry and academia due to their exceptional practicable applications in various electronic devices. In this work, pure AgNWs in the absence of nanoparticles are synthesised through chemical reduction method at low temperature 80 °C. AgNWs are produced based on the reaction of a reducing agent of tannic acid and a capping agent of polyvinylpyrrolidone (MW ≈ 1,200,000). The purity of the as-prepared AgNWs is improved in the presence of both chemical reactants. The controllable morphologies and sizes make the AgNWs grown steadily up to ∼30 μm in length with up to ∼58 nm in diameter. To enhance the yield of AgNWs, variations in the silver nitrate precursor (AgNO3) concentration in the synthesis of AgNWs are highlighted. The properties of the synthesised AgNWs are characterised through scanning electron microscopy (SEM), photoluminescence spectroscopy and UV–visible absorption spectroscopy. The overall properties of the AgNWs in terms of scattered light intensity and the transmittance of optical responses were largely improved as compared to other reported studies.